Smart Cities and Sustainable Urban Mobility: An Analysis of Urban Indicators of Marau/RS - Antunes, Eduardo Fernandes; Bertoni, Amanda Schüler; Ribeiro, Lauro André; Silva, Thaísa Leal da (National Journal of City Management, 2024)
The increasing problems related to urban mobility in Brazilian municipalities, caused mainly by uncontrolled urbanization and constant growth in the automotive vehicle fleet, is directly related to the difficulties presented in the public management of Brazilian cities, mainly with regard to urban planning. The objective of this article is to analyze users’ satisfaction of the urban mobility system in a small municipality, as well as the condition of the city’s physical characteristics, mainly identifying those that interfere with urban mobility, checking the most used modes in each sector of the city of Marau/RS and the mobility situation by age group and income, finding existing problems in each of the modes. To this end, a documentary survey was carried out on the object of study, a physical survey of the characteristics of the municipality, and a questionnaire with 84 respondents. The results obtained reveal the use of private cars as the main means of daily transport, correlated with low incentives and accessibility to sustainable modes of transport.